Hubungan Optimisme Dengan Resiliensi Pada Mahasiswa Kedokteran Universitas Malahayati Yang Sedang Menempuh Skripsi - SIti Hana Muthliatul Jannah; Supriyati; Arti Febriyani Hutasuhut; Octa Reni Setiawati (CV. Jasa Sukses Abadi, 2022)
Reseliensi is a process of human self-resilience that experiences trials in life, such as in students who are taking thesis. One of the factors that can affect resilience is optimism. When the student is taking the thesis, the student must do the process of self-resilience. So that students who are taking thesis are expected to have high resilience. Knowing the relationship of optimism with resilience in university medical students evenayati who are taking thesis class of 2018. This type of research uses a quantitative approach in which there are two psychological scales including optimism scale and resilience scale. The sample in this study, students of the Malahayati University Medical Study Program who were taking the class of 2018 thesis amounted to 111 people. Analyze the data using spearman's correlation test. The majority of students of the Malahayati University Medical Study Program who are taking the class of 2018 thesis have a moderate optimism of 72 people (64.9%). The majority of students of malahayati University Medical Study Program who are studying thesis class of 2018 have a high resilience of 89 people (80.2%). There is a relationship of optimism with resilience in students of the Malahayati University Medical Study Program who are studying the class of 2018 thesis with a correlation (r) between optimism and resilience of 0.319 with a significant level of 0.001. There is a relationship of optimism with resilience in students of the Malahayati University Medical Study Program who are taking the class of 2018 thesis with a correlation (r) between optimism and resilience of 0.319 with a significance level of 0.001.